The Interim application of EOT from 23” April, 2018 to 20''‘ map 2018 our Ref: BUCG-ABC JV-JAA-014 - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding the interim application of EOT from 23” April, 2018 to 20''‘ map 2018 our Ref BUCG-ABC JV-JAA-014 of Brac University new campus development project .